Financing concentration and credit risks: empirical study on the Islamic banks in Malaysia / Abdulazeez Adewuyi Abdurraheem, Md. Mahmudul Alam and Farah Aida Ahmad Nadzri - Abdurraheem, Abdulazeez Adewuyi; Alam, Md. Mahmudul; Ahmad Nadzri, Farah Aida (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
Sectoral financing concentration in a few sectors of the economy by Islamic banks in Malaysia has become a recurring issue. The objective of this study was to examine the relationship between financing concentration and Islamic banking credit risks in Malaysia. The study employed the Hirschman-Herfindahl-Index (HHI) to investigate the sectoral concentration of the financing portfolio. Dynamic OLS Approach of Cointegration was estimated to determine the long-run relationship between financing concentration and credit risks in the Islamic banking system. The HHI indicated that Islamic banks in Malaysia held a highly concentrated financing portfolio during the period 2007-2018. The result of the Dynamic OLS Approach of Cointegration indicated the existence of the long-term relationship between the banks’ financing concentration and credit risks. Findings from the study present practical implications for policy formulation and monitoring functions of the regulatory authorities, and managers of Islamic banks in particular, to protect the interests of depositors and the financial system against the consequences of an unanticipated macroeconomic shock. The study provides new insights into financing concentration as a determinant of credit risk in Islamic banking in Malaysia using static and dynamic statistical methods.